Patient-centered evaluation of an expectation-focused intervention for patients undergoing heart valve surgery: a qualitative study - Clifford, Caroline; Girdauskas, Evaldas; Klotz, Susanne G. R.; Kurz, Saskia; Löwe, Bernd; Kohlmann, Sebastian (Frontiers in Cardiovascular Medicine, 2024)
Objective Randomized controlled trials demonstrate the effectiveness of expectation-focused interventions in improving recovery outcomes following cardiac surgery. For dissemination in routine health care, it is important to capture the perspective of affected individuals. This qualitative study explores the perceived benefits and intervention-specific needs of patients who received expectation-focused intervention in the context of heart valve surgery. In addition, it explores potential barriers and adverse effects. Methods As part of an Enhanced Recovery After Surgery (ERAS) program within a multicentered randomized controlled trial, patients undergoing minimally invasive heart valve surgery received an intervention focused on their expectations. Six weeks after the intervention, semi-structured interviews were conducted with 18 patients to assess its feasibility, acceptance, barriers, benefits, and side effects. The transcribed interviews were analyzed using qualitative content analysis. Results The results indicate that both the intervention and the role of the patient and psychologist are key aspects in evaluating the expectation-focused intervention. Five key themes emerged from the patients’ perspective: personal needs, expectations and emotions, relationship, communication, and individuality. Patients valued the preparation for surgery and recovery and the space for emotions. Establishing a trustful relationship and addressing stigmatization were identified as primary challenges within the intervention. Conclusion Overall, patients experienced the expectation-focused intervention as helpful and no adverse effects were reported. Perceived benefits included enhanced personal control throughout the surgery and recovery, while the potential barrier of stigmatization towards a psychologist may complicate establishing a trustful relationship. Addressing personal needs, as a relevant topic to the patients, could be achieved through additional research to identify the specific needs of different patient subgroups. Enhancing the expectation-focused intervention could involve the implementation of a modular concept to address individual needs better.